Interfacial sites in platinum−hydroxide−cobalt hybrid nanostructures for promoting CO oxidation activity. Issue 4 (22nd January 2021) - He, Wenxue; Huang, Li; Liu, Chengyong; Wang, Siyu; Long, Zhixin; Hu, Fengchun; Sun, Zhihu
Abstract : This work demonstrates the promotional effect of Pt–OH–Co interfacial sites in hybrid nanostructures towards CO catalytic oxidation. Abstract : Metal–oxide/hydroxide hybrid nanostructures provide an excellent platform to study the interfacial effects on tailoring the catalysis of metal catalysts. Herein, a hybrid nanostructure of Pt@Co(OH)2 supported on SiO2 was synthesized by incipient wetness impregnation of Co(OH)2 with the aid of H2 O2 and successive urea-assisted deposition−precipitation of platinum nanoparticles. The Fenton-like reaction between Co2 + and H2 O2 during the impregnation process facilitates the formation of active interfacial sites. This hybrid nanostructure exhibits much higher catalytic activity towards CO oxidation than Pt/SiO2 nanoparticles with a similar Pt loading and particle size. In situ diffuse reflectance infrared Fourier transform spectroscopy was used to track the CO adsorption processes and to identify the reaction intermediates during CO oxidation. It shows that the OH species at the Pt–OH–Co interfacial sites could readily react with CO adsorbed on neighboring Pt to yield CO2 by forming *COOH intermediates and oxygen vacancies. Under the CO + O2 oxidation conditions, O2 molecules are activated by the oxygen vacancy and react with the CO molecules adsorbed on Pt to generate CO2, via forming the highly active *OOH intermediates as observed by DRIFTS.